SDSS-IV MaNGA: the indispensable role of bars in enhancing the central star formation of low-z galaxies. Issue 1 (23rd September 2020) - Lin, Lin; Li, Cheng; Du, Cheng; Wang, Enci; Xiao, Ting; Bureau, Martin; Fraser-McKelvie, Amelia; Masters, Karen; Lin, Lihwai; Wake, David; Hao, Lei
ABSTRACT: We analyse two-dimensional maps and radial profiles of EW(H α ), EW(Hδ A ), and Dn (4000) of low-redshift galaxies using integral field spectroscopy from the MaNGA survey. Out of ≈1400 nearly face-on late-type galaxies with a redshift z < 0.05, we identify 121 "turnover" galaxies that each have a central upturn in EW(H α ), EW(Hδ A ), and/or a central drop in Dn (4000), indicative of ongoing/recent star formation. The turnover features are found mostly in galaxies with a stellar mass above ∼10 10 M⊙ and NUV – r colour less than ≈5. The majority of the turnover galaxies are barred, with a bar fraction of 89 ± 3 per cent. Furthermore, for barred galaxies, the radius of the central turnover region is found to tightly correlate with one-third of the bar length. Comparing the observed and the inward extrapolated star formation rate surface density, we estimate that the central SFR have been enhanced by an order of magnitude. Conversely, only half of the barred galaxies in our sample have a central turnover feature, implying that the presence of a bar is not sufficient to lead to a central SF enhancement. We further examined the SF enhancement in paired galaxies, as well as the local environment, finding no relation. This implies that the environment is not a driving factor for central SF enhancement in our sample. Our results reinforce both previous findings and theoretical expectation that galactic bars play a crucial role in the secular evolution of galaxies by driving gas inflow and enhancing the star formation and bulge growth in the centre.